Trigeminocardiac Reflex in a Child During Pre-Onyx DMSO Injection for Juvenile Nasopharyngeal Angiofibroma Embolization: A Case Report - Puri, A.S. (Centauro S.r.l., 2011)
We describe the occurrence of the trigeminocardiac reflex (TCR) during DMSO pre-flushing of the microcatheter in preparation for Onyx embolization via the internal maxillary artery. TCR has not been previously associated with embolization of extradural entities. Familiarity with this clinical reflex and its proper management may help in planning neurointerventional procedures involving DMSO injection in the trigeminal territory.